Meningkatkan Aktivitas Belajar Digital Siswa Melalui Model Pembelajaran Berbasis Masalah Pada Mata Pelajaran IPA Kelas V MIN 15 Stabat T.A 2019/2020 - Gita Dwi Wardani (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
The purpose of this study was to increase students' online learning activities by using a problem-based learning model in science subjects with material on diseases attack human respiratory organs in class V MIN 15 Langkat T.A 2019/2020. This type of research is "Classroom Action Research" (CAR). The study was conducted in class V MIN 15 Langkat T.A 2019/2020, totaling 30 students, consisting of 17 boys and 13 girls. This research consists of two cycles and is divided into four stages, namely planning, implementing actions, observing and reflecting. Data collection technology was carried out by observing teacher and student activities, as well as questionnaires about student learning activities. The results showed that the use of problem-based learning models can improve student learning activities, namely the results of data analysis obtained from the learning activity observation sheet in the first cycle of 30 students, namely there are inactive categories as many as 22 students with a percentage (73%), and active categories. as many as 8 students with a percentage (27%). Then it increased in the second cycle with the inactive category of 1 student with a percentage (1%), and the active category as many as 29 students with a percentage (99%).